The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1002/ejoc.201300935
|View full text |Cite
|
Sign up to set email alerts
|

Furo[2,3‐c]pyrans from a Vinyl Sulfone Modified Methyl 2,6‐O‐Anhydro‐α‐D‐hexopyranoside: An Experimental and Theoretical Investigation

Abstract: A vinyl sulfone modified bicyclic sugar molecule undergoes efficient Michael addition of hetero‐ and carbon nucleophiles to afford single diastereomers. The same molecule consisting of two other masked functional groups, namely an aldehyde and an oxocarbonium ion, turned out to be a unique synthetic intermediate. The adducts generated from this Michael acceptor and a series of β‐dicarbonyl compounds and related reagents after acid treatment afforded a new class of furo[2,3‐c]pyrans, forming up to three new bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Although 11 and 12 were the expected products, the formation of a C2‐C3 double bond by the cleavage of C2‐N bond indicated that under “certain” reaction conditions the C2‐N bond of 10 would also act as a leaving group. This observation was significantly different from the reaction pattern of the oxo‐analogue 1 a (Scheme ) and prompted us to have a relook at the strategy. Therefore, in addition to the expected route indicated in scheme 2 (cleavage of C5‐O bond), another pathway, namely C2‐N bond cleavage is proposed (Figure ).…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…Although 11 and 12 were the expected products, the formation of a C2‐C3 double bond by the cleavage of C2‐N bond indicated that under “certain” reaction conditions the C2‐N bond of 10 would also act as a leaving group. This observation was significantly different from the reaction pattern of the oxo‐analogue 1 a (Scheme ) and prompted us to have a relook at the strategy. Therefore, in addition to the expected route indicated in scheme 2 (cleavage of C5‐O bond), another pathway, namely C2‐N bond cleavage is proposed (Figure ).…”
Section: Resultsmentioning
confidence: 75%
“…Interestingly, when compounds 14 b ‐ c were treated with much stronger triflic acid (TfOH; pKa=‐14) instead of TFA (pKa=0.23), yet another new class of aza‐tricyclic derivatives 17b–c was obtained in moderate yields along with 10–12 % of 16b–c as side‐products (Scheme ). The identities of furopiperidine derivatives 16a–c were determined by comparing their spectral data with those of furopyrans [Scheme ; 2 a : Y=Me (4 a) or OMe (4 b) or OEt (4 c) ] . In 1 H‐NMR spectra aldehydic, vinylic and methine protons of furopyrans and furopiperidines resonated at comparable regions (see SI; Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations